Efforts To Empower The Bhabinkamtibmas Blora Police In Supporting Health Protocols During The Covid-19 Pandemic - Adi Nur Sholeh, S.H (Jurnal Hukum dan Sosial Politik, 2023)
Currently, Covid-19 is a major problem that is being faced by almost the entire world, including Indonesia. The Covid-19 pandemic in Indonesia has multi-sectoral impacts from various aspects, namely health, education, social and economy, including what happened in Blora Regency. Synergy with various parties such as Babinsa, village midwives, village heads and village officials is needed to support health protocols, besides the active role of the National Police in this case Bhabinkamtibmas (Bhayangkara builder of security and public order) is very important in efforts to control the spread, minimize prevention and provide education as well as information to the public regarding Covid-19 in order to create a conducive security and social order situation. The empowerment of the Blora Police bhabinkamtibmas in the target villages or sub-districts has been going well considering the condition of the Covid-19 pandemic in Blora Regency is increasing every day but is not matched by public awareness to comply with the health protocols applied.